Reducing the Cost of Calculations for Incremental Dynamic Analysis of Building Structures Using the Discrete Wavelet Transform. Issue 7 (19th May 2022) - Dadkhah, Masoud; Kamgar, Reza; Heidarzadeh, Heisam
ABSTRACT: The method of incremental dynamic analysis (IDA) is one of the most accurate nonlinear seismic analyses. IDA is a time-consuming method and has a high computational cost. Also, an IDA curve should be obtained from the building analysis subjected to a series of earthquakes that should cover all regions of the structural responses. In this paper, the discrete wavelet transform is used to solve these problems. The results showed that the use of the filtered records reduces the computational cost and time about 87.4% and 73%, respectively, while the maximum error is just about 7.6%.